The Effectiveness of Cognitive Behavioral Therapy on Reducing Symptoms of Depression, Pain Intensity, and Movement Limitation in Patients with Rheumatoid Arthritis - Paknahad, NazAfarin; Kordmirza Nikoozadeh, Ezzatollah; Saffarinia, Majid; Rostamian, Abdulrahman (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim:Rheumatoid arthritis is a disease that due to pain in the patient’s joints, the patient cannot make strong movements due to the muscles around the joints are weakened and the patient’s movement capability is reduced. Thus, this disease is associated with pain, depression, and also movement disability. Materials and Methods:This research is in the qualitative part of a semi-experimental design with a pre-test and post-test with a control group. The statistical population included people suffering from rheumatoid arthritis. In the quantitative part, based on the size of the population, 30 women with rheumatoid arthritis were and randomly replaced in the experimental and control groups. The experimental group in this study underwent cognitive behavioral therapy. The required information was collected by Beck’s Depression Questionnaire, McGill Pain Intensity Questionnaire (SF-MPQ-2), Osostria ODI Questionnaire, Physical Disability Assessment Questionnaire (Rowland & Morris, 1983), and Quebec Pain Disability Scale (QPDS). Also, for the measurement level of the desired variables and hypotheses, descriptive statistics such as mean, standard deviation, frequency distribution tables, and graphs were used in the descriptive section. In the inferential part, the assumptions of univariate and multivariate covariance analysis, Levine’s test, and Sphericity were used. Results:The results of univariate and multivariate analysis of covariance showed that CBT reduces depression, pain, and their components; Motor disability, components of functional disability, physical disability, and back pain disability were effective in patients with rheumatoid arthritis. It was also stated that CBT has a higher effectiveness in reducing pain and its components (except emotional perception of pain) in patients with rheumatoid arthritis. Conclusion:CBT has been effective in all four variables.